IMPLEMENTASI HIPNOTERAPI BERBASIS KARMA TATTWA PADA YAYASAN PASRAMAN KARMADATU DI KARANGASEM BALI - Ni Luh Putu Lasmini; I Gede Suwindia; I Wayan Gata (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2022)
Various phenomena that occur a lot in society are phenomena of people who have materialistic tendencies, prioritizing the interests of finding and hoarding property for the satisfaction and needs of their life. So that sometimes they do not consider or pay attention to the health and safety of themselves and others. Very little time is set aside to pay attention to his physical and mental health such as exercising, contemplating or meditating so it is undeniable that his soul and physique are easily fragile. All methods and opportunities are used only to work and work for the sake of obtaining wealth, position and power so that when they are hit by problems they cannot overcome them alone and then seek help from others at a cost that is also not small. The results of the study show that (1) the implementation of hypnotherapy based on the teachings of karma tattwa in developing human mentality is by (a) understanding the teachings of Karma Phala or Karma Tattwa (b) hypnotherapy techniques from apperception, suggestion and reflection to extract the findings. (c) Techniques for building the human mentality by interviewing, deepening the subconscious, and directing the situation and psychological condition to be comfortable. (2) There are many types of physical and psychological complaints that have been handled. Leading into the client's subconscious, and reflection. Sauca self-cleansing, Sadhana and serenity meditation over a period of time ranging from 3 times to a repetition of 108 times in a mantra Sadhana. (3) The impact is (a) psychological improvement (b) has an impact on physical health (c) has an impact on increasing religious emotions and (d) increases one's spirituality with a stable psychological, physically healthy and religious emotions have increased, so strength appears to love others, to serve, to feel bad things and good things will happen and also to be able to feel the feelings and hearts of others.Keywords: Implementation, Hypnotherapy, Karma Tattwa